Radix formation between median and musculocutaneous nerves: embryological, morphological and clinical correlation - D, Suseelamma; K, Krishna Chaitanya; HR, Sharada; S, Deepthi (International Journal of Research in Medical Sciences, 2017)
In ours study we report radix formation between median nerve and musculocutaneous nerves. The study was conducted in the Department of Anatomy, Kamineni Institute of Medical Sciences, Narketpally, Nalgonda Dt., Andhra Pradesh, India. During routine cadaveric dissections in the upper limbs, we observed an anastomosis (radix) between median and musculocutaneous nerves in the arm. Variations in the origin, course, branching pattern, communications was observed. These variations have clinical significance in brachial plexus block and surgical procedures.